2012
DOI: 10.3184/174751912x13333849411283
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Potent Anticancer Thieno[2,3-d]Pyrimidine Derivatives

Abstract: As part of our program to identify novel cytotoxic agents, various series of hexahydrocycloocta [4,5]thieno [2,3-d] pyrimidines and pyrimidin-4-ones substituted by aryl at the C-2 position together with phenylethylamino, substituted amino, hydrazinyl or arylidenhydrazinyl substituents at the C-4 position were synthesised. These compounds were prepared as bioisosteres of gefitinib, an antitumour drug used for the treatment of gastrointestinal stromal tumours. All compounds exhibited antitumour activity agains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Ivachtchenko et al .11 reported that the amino-thiophene ester (22) was reacted with thiophosgene to generate isothiocyanate (28).…”
Section: Methodsmentioning
confidence: 99%
“…Ivachtchenko et al .11 reported that the amino-thiophene ester (22) was reacted with thiophosgene to generate isothiocyanate (28).…”
Section: Methodsmentioning
confidence: 99%
“…A range of thienopyrimidines 49 , thienotriazones 50 , and thienodiazepinones 51 have been prepared from 2‐aminothiophenes by standard methods (Figure ) . These compounds featured potent antitumor properties, but have not been specifically tested for activity toward the PAFr.…”
Section: Synthesis Of Pafr Antagonistsmentioning
confidence: 99%
“…However, thiophene-and furan-fused heterocycles are not common. [118][119][120] For the synthesis of furo-fused diazepinones, the monoacid 141 was treated with oxalyl chloride followed by amines to give amides 319. The ester functionality in 319 was first converted into the corresponding acyl azide 321 via 320.…”
Section: Diazepinone Derivativesmentioning
confidence: 99%